EFFECT OF APPLICATION OF GREEN ACCOUNTING AND CORPORATE SOCIAL RESPONSIBILTY AGAINST COMPANY VALUE AT MANUFACTURING COMPANY - Amelia Wahyu Erwanto (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
This study tests and analyzes how implementation of green accounting and corporatesocial responsibility on firm value in manufacturing companies basic industrial andchemical sectors listed on the Indonesia Stock Exchange in 2020-2022. The data camefrom the Indonesian Stock Exchange’s annual report which was published. Twelvemanufacturing companies in the basic industrial and chemical that were listed on theIndonesian Stock Exchange in 2020-2022 serve as the study’s sample. Data analysis wasdone using SPSS version 26. The implementation of green accounting and corporatesocial responsibility have a favorable and significant association, according to researchfindings. However the green accounting variable has a negative impact on firm valuewhereas the corporate social responsibility varaible has positive impact on firm value.